Design, construction, and testing of an open-loop low-speed wind tunnel - Muhammad Adnin, Mat Bahari (2012)
An open-loop low-speed wind tunnel is one of the easiest ways to study about aerodynamics for undergraduate studies. The objectives of this project are to propose a design with detail analysis, fabrication of a small scale open-loop low-speed wind tunnel and to validate the designed wind tunnel through performance testing with the existing instrumentations available in the laboratory. The wind tunnel was designed by considering the essential parts of the wind tunnel with the proper justifications before modelled with Computer Aided Design (CAD) and then tested using the Computational Fluid Dynamics (CFD). After obtaining the desired simulation result, the designed wind tunnel was fabricated and then followed by the test models. Then the wind tunnel undergoes the performance testing for validation and calibration. For the Ahmed Body flow pattern testing, the flow behaves just like the flow pattern tested in calibrated wind tunnel. For the case study testing, a cylinder model was used and the highest flow speed is 0.4317 m/s while the slowest flow speed is 0.1401 m/s. However for the case study experiment, the result obtained is not at its best condition as there is wake flow generated around the cylinder body and further improvement is required to obtain the undoubtedly results.